Genetic diversity of Jatropha curcas L. genotypes: a potential biofuel crop in Bangladesh. Issue 2 (25th January 2022) - Chakrabarty, S.; Islam, A. K. M. Aminul; Sultana, Nasrin; Chakraborty, P.
Abstract: Jatropha curcas L. is a potential biofuel crop grown in the tropics and subtropics. The present study was conducted to enumerate the genetic diversity of 17 morpho-agronomic traits of 45 Jatropha genotypes from Bangladesh during 2015–2017. Analysis of variance revealed sufficient genetic variation among the genotypes for all the traits. High broad-sense heritability coupled with high genetic advance as a percentage of the mean were observed for seed yield per plant and related traits. Correlation coefficients indicated that total number of inflorescences, number of male flowers per inflorescence, number of female flowers per inflorescence, number of fruits per inflorescence, number of seeds per inflorescence, weight of mature fruits per inflorescence, weight of dry fruit per inflorescence and weight of dry seeds per inflorescence were highly correlated with seed yield per plant. The first four principal components explained 81.2% of the total variation. Cluster analysis based on Euclidean distance indicated the highest intra-cluster distance in cluster II and the highest inter-cluster distance between clusters II and VI. Based on this study, it is suggested that hybridization of parents between clusters II and VI will produce noble hybrids that will increase the potential for biofuel production.